Prevalence and associated factors of eight antenatal care contacts among mothers who give birth in Shebel Berenta district, East Gojjam zone, northeast Ethiopia, 2024 - Abebaw, Nigusie; Negesse, Yezbalem; Begashw, Asnake; Amare, Dagnachew; Tsegaw, Genet; Meshesha, Dessalew; Geto, Kefale (Frontiers in Reproductive Health, 2025)
IntroductionAntenatal care refers to the medical attention provided by skilled healthcare professionals to pregnant women to ensure optimal health outcomes for both the mother and fetus throughout pregnancy. In Ethiopia, there is limited evidence regarding the completion of eight antenatal care contacts and the factors associated with it. Therefore, the aim of this study was to assess the prevalence and associated factors of completing eight antenatal care contacts among mothers in Shebel Berenta Woreda.MethodA community-based cross-sectional study was employed. A stratified sampling technique was employed to select the sample. Data were exported from Kobo Toolbox software to SPSS version 27 for analysis. Bivariable and multivariable logistic regression analyses were used to assess associations between the outcome and independent variables, with statistical significance determined at a p-value of <0.05.ResultThis study showed that the prevalence of eight or more antenatal care contacts was 9.6% [95% confidence interval (CI): 7.4–12.3]. In this study, good knowledge of ANC [adjusted odds ratio (AOR) = 2.402; 95% CI: 1.115–5.175], media exposure (AOR = 2.47; 95% CI: 1.15–5.306), time of early initiation for first ANC contact (AOR = 5.46; 95% CI: 2.837–10.51), women's governmental occupation (AOR = 3.745; 95% CI: 1.364–10.28), two to four pregnancies (AOR = 3.524; 95% CI: 1.696–7.32), and family size less than five (AOR = 3.005; 95% CI: 1.461–6.179) were significantly associated with the outcome variable.ConclusionThe study indicates that the prevalence of eight or more antenatal care contacts was low. Time of initiation for first ANC contact, women's occupational status, knowledge of antenatal care, family size, number of pregnancies, and media exposure were significantly associated with the outcome variable.